The Influence of Gender In Using Mobile Payments - WENDI SOUISA (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
T Mobile payments have been proposed as a way to promote micropayments in electronic and mobile commerce and as an alternative to reduce the use of cash. This study aims to examine the influence of gender on the intention to make payments via mobile, with a sample of 100 students of the Commercial Administration study program, and the Accounting study program from the Ambon State Polytechnic, Data analysis techniques used using PLS. This study found that women's behavioral intentions were significantly influenced by performance expectations and for men there was no significant influence of performance expectations on behavioral intentions in using mobile payments, it was also found that women's behavioral intentions were significantly influenced by higher social norms than men in using mobile payments, the influence of facility conditions in using mobile payments was more significant on Women versus men are not significant, and a significant effect of price value is also found in women's intention to use mobile payments while this does not affect men's intention to use mobile payments.